2003
DOI: 10.2166/wst.2003.0017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt concentration on floc characteristics and pollutants removal efficiencies in treatment of seafood wastewater by SBR

Abstract: Most seafood wastewater has been treated by the activated sludge process. Due to changes in salt concentration, pollutant loadings and raw materials, the process is not operated satisfactorily to meet effluent regulation. Most problems faced at present are solid liquid separation. In this study, effects of salt concentration on floc characteristics and pollutants removal efficiencies were investigated in treatment of seafood wastewater by SBR. For analyzing fractal dimension of flocs, the small angle laser lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Dahl et al [20], treating in a nitrifying system wastewater with high salinity (20 g Cl − L −1 ) and ammonia concentration of 120 mg NH 4 + -N L −1 , obtained a sludge with a SVI of 32 mL g VSS −1 . In other cases a negative effect was observed like in the case of Moon et al [21]. These authors found floc size decreased and settling properties deteriorated with increasing salt concentration when they treated seafood wastewater with a SBR at NaCl concentrations up to 10 g L −1 .…”
Section: Biomass Characteristicsmentioning
confidence: 88%
“…Dahl et al [20], treating in a nitrifying system wastewater with high salinity (20 g Cl − L −1 ) and ammonia concentration of 120 mg NH 4 + -N L −1 , obtained a sludge with a SVI of 32 mL g VSS −1 . In other cases a negative effect was observed like in the case of Moon et al [21]. These authors found floc size decreased and settling properties deteriorated with increasing salt concentration when they treated seafood wastewater with a SBR at NaCl concentrations up to 10 g L −1 .…”
Section: Biomass Characteristicsmentioning
confidence: 88%
“…Furthermore, filamentous bacteria, which are very important for the aggregates' structure, are also known to be highly sensitive to NaCl presence. It was already verified by several authors that with NaCl addition, the osmotic stress on microbial cells decreases the flocculation abilities (Moon et al 2002;Campos et al 2002). Hence, certain species of microorganisms may have been reduced, due to osmotic stress, leading to the release of their cellular components and thus increasing turbidity levels.…”
Section: Settling Propertiesmentioning
confidence: 92%
“…The existence of salt in wastewater reduces the populations of protozoa, resulting in higher dispersed bacteria contents, as most protozoa graze on bacteria, and lower sludge settling ability due to the fact that protozoa, on the course of their motion, break up the larger flocs. When the salinity of an effluent increases, the reduction of filamentous bacteria occurs (da Motta et al 2001), decreasing also the mechanical integrity and structure of the aggregates (Moon et al 2002). In the present work, the biomass structure response to a salinity increase was investigated based on the SVI and turbidity measurements.…”
Section: Settling Propertiesmentioning
confidence: 99%
“…Some studies have been conducted on the degradation of complex wastewater using halophiles in SBR Irvine 1994, 1995;Kubo et al 2001;Moon et al 2002;Uygur and Kargi 2004;Lefebvre et al 2004). In this study, the salt-tolerant microorganism used by Senthilkumar et al (2008) for the treatment of tannery wastewater was used in a SBR.…”
Section: Introductionmentioning
confidence: 99%